Teacher researchers as writers: a way to sharing findings - Cárdenas, Melba Libia (Colombian Applied Linguistics Journal, 2003)
A teacher development programme (TDP) for teachers of English at the Universidad Nacional de Colombia in Bogotá has incorporated the research element as a means to motivate practitioners to widen professional knowledge. Based on the assumption that research findings gain real value if shared with other people, teachers have been challenged to establish a dialogue with academic communities by writing formal reports required by the University and articles describing the research processes they have accomplished. This paper examines the experiences of teacher researchers as writers as revealed in a research project in progress. I start by providing some background information about the TDP and then refer to the criteria that helped us to complete the writing tasks. Difficulties and strategies used to overcome them are also pointed out. Finally, I mention the benefits teachers identified after publishing their research reports in the PROFILE journal as well as some pedagogical implications.